Economic development instruments employed following the closure of an industrial plant – the example of Polish municipalities - Cybulska Magdalena (Miscellanea Geographica: Regional Studies on Development)
This article addresses the issue of the impact of industrial plant closures on the economic policies currently being pursued in Polish municipalities. The survey indicated differences between municipalities that have experienced industrial plant closures and those that have not. The nonparametric Mann–Whitney U test indicated statistically significant differences in the overall approach of municipalities to the economic policies currently being implemented (attracting large and foreign investors), and in their use of several economic development instruments – namely, investment fairs, business incubators, investor services at the office and job activation programmes. The results show the importance of instruments for shaping the local labour market and indicate areas of support that are also relevant from above the local level in terms of territorial policy objectives.